2005
DOI: 10.1177/107424840501000108
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Extracellular Acidosis on the Effect of IKr Blockers

Abstract: Our data show that the Ikr blocking effect of azimilide, dofetilide, and quinidine was attenuated at acid pH, whereas this was not the case for amiodarone. These observations may explain the efficacy of amiodarone in reducing arrhythmic death in patients after a myocardial infarction compared with other IKr blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
6
18
0
Order By: Relevance
“…It is possible that the binding of extracellular protons might have attenuated the effects of nifekalant by modulating its binding property. This explanation is indirectly supported by a report that acidic conditions do not affect hERG IC 50 of amiodarone, since amiodarone is known to bind to a different site of hERG channels compared with other I Kr blockers whose IC 50 was increased under acidic conditions (11). Thus, the attenuation of pharmacological effects of nifekalant under acidic conditions as observed in this study might be due to the decrease in accessibility to I K1 channels by increased ionization of nifekalant and/or the interruption of the binding of nifekalant to I Kr channels by proton binding.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It is possible that the binding of extracellular protons might have attenuated the effects of nifekalant by modulating its binding property. This explanation is indirectly supported by a report that acidic conditions do not affect hERG IC 50 of amiodarone, since amiodarone is known to bind to a different site of hERG channels compared with other I Kr blockers whose IC 50 was increased under acidic conditions (11). Thus, the attenuation of pharmacological effects of nifekalant under acidic conditions as observed in this study might be due to the decrease in accessibility to I K1 channels by increased ionization of nifekalant and/or the interruption of the binding of nifekalant to I Kr channels by proton binding.…”
Section: Discussionsupporting
confidence: 63%
“…Meanwhile, with regard to the shortening of MAP duration, some studies reported that a decrease in extracellular pH shortens the action potential duration (22 -25), but the others described opposite results (26,27). It has been reported that under acidic condi- tions, H + directly binds to I Kr and I Ca channels, resulting in their current inhibitions (11,19,20,28). Inhibition of I Kr channels causes the prolongation of MAP duration, whereas inhibition of I Ca channels leads to its shortening.…”
Section: Discussionmentioning
confidence: 99%
“…However, not only extracellular potassium elevates during an ischemic episode, the extracellular acidosis also develops. In another set of experiments, we found that IKr-blocking action of sotalol was significantly decreased at acidic condition, but not that of amiodarone [29]. Our data show that the IKr inhibition and action potential-prolonging effect of amiodarone can be retained with extracellular acidosis and hyperkalemia.…”
Section: Discussionmentioning
confidence: 71%
“…When patients on I Kr -blocking antiarrhythmic drugs drink citrus juices, the additional I Kr inhibition by naringenin from the citrus juice may lead to excessive QT prolongation, and thus the risk of developing arrhythmias. This may be especially the case when the patient has metabolic and electrolyte disorders such as hypokalemia [16, 24], cardiac ischemia with resulting regional acidosis and hyperkalemia [25,26,27], or a congenital defect in the potassium channel [28]. …”
Section: Discussionmentioning
confidence: 99%